2016
DOI: 10.3892/mmr.2016.5203
|View full text |Cite
|
Sign up to set email alerts
|

Shensong Yangxin capsules prevent ischemic arrhythmias by prolonging action potentials and alleviating Ca2+ overload

Abstract: Shensong Yangxin capsules (SSYX) are an effective traditional Chinese medicine that has been used to treat coronary heart disease clinically. The present study aimed to establish whether SSYX prevent ischemic arrhythmias in rats, and to explore the underlying mechanisms. Male rats were pretreated with distilled water, SSYX and amiodarone for one week. Acute myocardial ischemia (AMI) was performed to induce ischemic arrhythmias. The incidence and severity of ischemic arrhythmias were evaluated. The action poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Patch-clamping of isolated ventricular myocytes has demonstrated that SSYX is a multichannel blocker with measurable effects on the fast sodium, L-type calcium channel, transient outward potassium (Ito), and inward rectifier potassium currents (IKr), resulting in an overall prolongation of the action potential [10, 11]. Similarly to our findings, sinus rates are increased with SSYX, although this increase is abolished with autonomic blockage with metoprolol and atropine [12].…”
Section: Discussionsupporting
confidence: 77%
“…Patch-clamping of isolated ventricular myocytes has demonstrated that SSYX is a multichannel blocker with measurable effects on the fast sodium, L-type calcium channel, transient outward potassium (Ito), and inward rectifier potassium currents (IKr), resulting in an overall prolongation of the action potential [10, 11]. Similarly to our findings, sinus rates are increased with SSYX, although this increase is abolished with autonomic blockage with metoprolol and atropine [12].…”
Section: Discussionsupporting
confidence: 77%
“…In our previous research, we demonstrated that bladder ICC-LC hyperactivity accounted for bladder hyperactivity in CYP-induced chronic cystitis, which was characterized by excessive Ca 2+ entry into cells upon carbachol application 12 . Furthermore, Ca 2+ overload in cardiomyocytes is closely related to cardiac dysfunction 37 , 38 . Thus, we suggest that abnormal Ca 2+ signaling in bladder ICC-LCs may be involved in the pathogenesis of bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that SSYX could reverse atrial electrical remodeling and the atrial fibrillation by adjusting the autonomic nerve activity and inhibiting atrial inflammation ( Zhao et al., 2017 ). Another study reported that SSYX could reduce acute myocardial ischemia (AMI)-induced VA by inhibiting transient outward K + current ( I to ) and reducing intracellular Ca 2+ concentration of the cardiomyocytes ( Zhao et al., 2016 ). Although SSYX may exert anti-arrhythmia effect by reversing electrical remodeling, until now, the role of SSYX in the setting of MetS-induced VA remains unclear.…”
Section: Discussionmentioning
confidence: 99%